Multi-environment genomic selection in rice elite breeding lines - Nguyen, Van Hieu; Morantte, Rose Imee Zhella; Lopena, Vitaliano; Verdeprado, Holden; Murori, Rosemary; Ndayiragije, Alexis; Katiyar, Sanjay; Islam, Md Rafiqul; Juma, Roselyne U.; Galvez, Hayde; Glaszmann, Jean-Christophe; Cobb, Joshua N.; et al. (Research Square Platform LLC, 2022)
Abstract Background: Assessing the performance of elite lines in target environments is essential for breeding programs to select the most relevant genotypes. One of the main complexities in this task resides in accounting for the genotype by environment interactions. Genomic prediction models that integrate information from multi-environment trials and environmental covariates can be efficient tools in this